O espaço social da operação lava jato e a mobilização linguística da corrupção pela mídia especializada - Francelin, Haron Barberio (Universidade Federal de São Carlos, 2023)
This dissertation analyzes the media translation of the Lava-Jato Operation from 03/04/2016 to 05/07/2018. For that, a previous study of the notions of corruption that are formulated within Social Science was necessary, having finally assumed a certain premise of corruption, this one associated with the phenomenon that circumscribes multiple agents, in a moment of crisis in the belief of the Official and the Universal , state support binomial. Such an event is punctual and offered in moments of double or triple game between many instances of the social world. In view of this selected configuration due to the concept of elites, the agents that participated in this social space and those statistically described through their social properties in order to make approximations and distances between them. With this background of the phenomenon, analyzed how the social agents of the media specialized in specific related in the construction of the Operation. Through the linguistic translation of the phenomenon, it can, in a sense, describe its positions taken and whether they reserved a corresponding previously articulated way of acting in this opportunity generated by the social space manifested in the crises of belief in the State instance.
The social space of the Lava Jato operation and the language of corruption by the specialized media
Keywords: Corrupção; Elites; Tradução; Mídia; CIENCIAS HUMANAS::CIENCIA POLITICA::ESTADO E GOVERNO